2020
DOI: 10.1090/conm/748/15056
|View full text |Cite
|
Sign up to set email alerts
|

Two classical properties of the Bessel quotient 𝐼_{𝜈+1}/𝐼_{𝜈} and their implications in pde’s

Abstract: Two elementary and classical results about the Bessel quotient yν = I ν+1 Iνstate that on the half-line (0, ∞) one has for ν ≥ −1/2: (i) 0 < yν < 1; (ii) yν is strictly increasing. In this paper we show that (i) and (ii) have some nontrivial and interesting applications to pde's. As a consequence of them, we establish some sharp new results for a class of degenerate partial differential equations of parabolic type in R n+1 + × (0, ∞) which arise in connection with the analysis of the fractional heat operator (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The final statement of the theorem follows from the observation that when z = 0, then in [22,Proposition 4.1,(4.3)] it is shown that for any a > −1, one has…”
Section: Functional Inequalities Etcmentioning
confidence: 95%
“…The final statement of the theorem follows from the observation that when z = 0, then in [22,Proposition 4.1,(4.3)] it is shown that for any a > −1, one has…”
Section: Functional Inequalities Etcmentioning
confidence: 95%
“…Adapting the same argument in Proposition 2.4 in [20], let a > −1, for every x, η ∈ R and every 0 < s, t < +∞ one has u(x, η, t + s) = +∞ −∞ u(x, y, t) u(y, η, s)|y| a dy.…”
Section: Fundamental Solution Of L Amentioning
confidence: 98%